2018
DOI: 10.1111/imcb.12032
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional heterogeneity of human intermediate monocytes based on HLADR expression

Abstract: Human blood monocytes are subclassified as classical, intermediate and nonclassical. In this study, it was shown that conventionally defined human intermediate monocytes can be divided into two distinct subpopulations with mid- and high-level surface expression of HLA-DR (referred to as DR and DR intermediate monocytes). These IM subpopulations were phenotypically and functionally characterized in healthy adult blood by flow cytometry, migration assays and lipoprotein uptake assays. Their absolute numbers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…of peripheral venous blood monocytes [164]. Previously, data have suggested heterogeneity among intermediate monocytes [126,173]. However, very recently, highdimensional mass cytometry data identified one intermediate subset [174], but this finding suggests there is some heterogeneity among classical monocytes [174].…”
Section: Monocyte-derived Endothelial Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…of peripheral venous blood monocytes [164]. Previously, data have suggested heterogeneity among intermediate monocytes [126,173]. However, very recently, highdimensional mass cytometry data identified one intermediate subset [174], but this finding suggests there is some heterogeneity among classical monocytes [174].…”
Section: Monocyte-derived Endothelial Cellsmentioning
confidence: 95%
“…Animal studies suggest that during a steady-state, classical monocytes replenish resident peripheral monocyte-derived cells [124,125]; these monocytes also show the highest migration in response to CCL2, CCL8, and CCL7 [126] and have a half-life in the circulation of less than one day in humans [115]. Monocytes are recruited to inflamed tissues at high rates, where they attract other immune cells by secreting cytokines and antimicrobial factors [127].…”
Section: Figure 2 Models Of Monopoiesis Model Amentioning
confidence: 99%
“…In individuals with stable atherosclerotic disease, an increased proportion of inflammatory monocytes is associated with elevated levels of lipoprotein a, which is a proatherogenic plasma lipoprotein 27) . Furthermore, lower HLA-DR expression in intermediate monocytes was associated with metabolic disorders 14) . These properties, along with their association with increased cIMT in our study, suggested that intermediate monocytes may be involved in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous data regarding peripheral monocytes' prognostic value remains controversial. Several studies have demonstrated a significant association between monocyte subsets and atherosclerosis plaque severity, vulnerability, and progression of CVD 7,8,[14][15][16][17] . Additionally, CD14 CD16 monocytes were associated with restenosis, after percutaneous transluminal angioplasty, in individuals with peripheral artery disease 18) .…”
Section: Discussionmentioning
confidence: 99%
“…HCC patients presented a significant decrease in the relative frequency and absolute numbers of circulating nonclassical monocytes, both at T0 and T1, when compared to the HG, and a significant increase in the relative frequency of classical monocytes, both at T0 and T1, as compared to the HG. Interestingly, the relative frequency of intermediate monocytes presenting high-level surface expression of HLA-DR [13] (HLADR ++ ) was significantly decreased in HCC patients at T0 in comparison to the HG (Table 1).…”
Section: Alterations Of Peripheral Blood Leukocyte Subsets In Cca Andmentioning
confidence: 99%